Python for finance : mastering data-driven finance - Hilpisch, Yves J. (O'Reilly Media, 2018)
The financial industry has recently adopted Python at a tremendous rate, with some of the largest investment banks and hedge funds using it to build core trading and risk management systems. Updated for Python 3, the second edition of this hands-on book helps you get started with the language, guiding developers and quantitative analysts through Python libraries and tools for building financial applications and interactive financial analytics. Using practical examples throughout the book, author Yves Hilpisch also shows you how to develop a full-fledged framework for Monte Carlo simulation-based derivatives and risk analytics, based on a large, realistic case study. Much of the book uses interactive IPython Notebooks.- Resumé vydavatel
Keywords: finanční inženýrství; zpracování dat; finance; statistické metody; Python (programovací jazyk); financial engineering; data processing; statistical methods; Python (programming language); elektronické knihy; monografie; electronic books; monographs